Microbial and chemical investigations of soils in organic and conventional farming in Nyírség region - Demeter, Ibolya; Makádi, Marianna; Aranyos, Tibor; Ferenczy, Antal; Posta, Katalin (JOURNAL OF LANDSCAPE ECOLOGY, 2013)
The maintenance of soil fertility is the base of food production. Fertility means not only the quantity of available nutrients, but it is closely related to the microbial activity, and physical and chemical properties of the soil as well. However the microbial community of soil -its diversity and quantity- is significantly influenced by the applied farming system, the shifts in microbial community also effect on soil fertility. Our aim was to determine the dynamics of organic matter and microbiological characteristics, and to study the relationship of these parameters in typical sandy and meadow soil samples in Nyírség region, under conventional and ecological farming systems. Invertase and catalase activity and soil chemical properties (pHKCl, carbon and nitrogen content, soil organic matter, nitrite-nitrate-N content) were examined and the correlation between them was studied in two soil depths. Our results of the samples of 2012showed that the invertase and catalase enzyme activity, and the carbon and nitrogen content of the soil decreased with depth. The different soil types and farming methods had significant effect on both enzyme activities. Higher level of enzyme activities as well as carbon and nitrogen content was found in sandy soil samples in organic farming and in meadow soil samples in conventional farming system.